Levels of physical fitness and analysis of posture tendencies in classic ballerinas - Alessandra Prati; Sérgio Prati (Universidade Federal de Santa Catarina, 2006)
Classic ballet is a dance practiced by children and adolescents along all their development process. To get to the high level of technique and performance, it is necessary more than seven years of practice. In this way, the repetition of the technical movements can promote the acquisition of some posture problems, as well as to develop aspects of the specific physical fitness. The aim of this descriptive study was to analyze physical fitness level and posture of ballet dancers. The sample was composed by eleven dancers with more than seven years of practice from ballet schools in Maringá, Paraná. For analysis of posture, the method PSU adapted by Althoff et al. (1988) was applied by using subjective evaluation through symmetrigraf view and deviations analyses of body segments (normal when index of postural correction -IPC>85%). Physical fitness level was determined by anthropometry to identify body composition (body mass index=BMI, % body fat, waist-to-hip ratio), strength test (dynamometry=D), arm strength (SA), abdominal resistance (AR), muscle power (vertical jump=VJ and long jump=LJ), the sit-and-reach test (Fl) and aerobic work capacity (12 minute test). The main results were mean body composition (BMI=19.9kg.m-2; % body fat=22.7% and waist-to-hip ratio=0.69) was appropriate to the activity. Strength and resistance (D=50.3kgf, SA=21, AR=23 and Fl=40cm), muscle power (VJI=36.8cm and LJ=136cm) and aerobic resistance (12min=1526m) mean values were lower than expected. It was noticed that the dancers presented mean IPC of 86,9%. The segment head and neck showed deviations (13% kyphosis), as well as upper and lower back region (8% hyperlordosis), abdomen and hip (13% protruding abdomen and one higher hip) and lower limbs (18% flat feet). The results lead to infer that the posture deviations observed can be consequence of the repetition of characteristic ballet movements along years of training. It is thought that for better performance in this long-term training and forminimizing risk for posture problems, the training should include general and specific physical fitness and also compensatory exercises for the ballet dancers. RESUMO O ballet clássico é uma modalidade de dança praticada por crianças e adolescentes ao longo de todo o seu processo de desenvolvimento. Para se chegar ao estágio de elevado desempenho técnico e performance são necessários mais de sete anos de prática. Nesse sentido, a repetição dos movimentos técnicos pode promover a aquisição de algumas tendências de postura, bem como desenvolver aspectos da aptidão física específica. O objetivo desse trabalho descritivo foi de analisar níveis de aptidão física e tendências posturais de bailarinas clássicas. A amostra foi composta por onze bailarinas clássicas (com mais de sete anos de prática) de escolas de ballet de Maringá. Para análise de tendências posturais foi utilizado o método PSU adaptado por Althoff et al. (1988) utilizando-se de avaliação subjetiva através de simetrógrafo e análise de desvios por seguimentos corporais (ideal quando ICP>85%). Para verificação dos níveis de aptidão física utilizou-se da análise de composição corporal por antropometria (IMC, %Gordura e relação cintura quadril=RCQ), testes de força (dinamometria=D), flexão de braços (FB), resistência abdominal (RA), potência muscular (impulsão vertical=IV e horizontal=IH), flexibilidade (Banco Well's=Fl) e potência aeróbica (Teste de 12'). Resultados principais foram: níveis médios de composição corporal (IMC=19,9kg/m2; %G=22,7% e RCQ=0,69) adequados à sua atividade; nos aspectos físicos, força e resistência (D=50,3kgf, FB=21, RA=23 e Fl=40cm), potência muscular (IV=36,8cm e IH=136cm) e capacidade aeróbica (12'=1526m) os resultados em média foram inferiores ao esperado. Quanto à postura, apresentaram em média índice de correção postural (ICP) igual a 86,9%, e tendência a desvios nas regiões da cabeça e pescoço (13% cifose), dorsal e lombar (8% hiperlordose), abdômen e quadril (13% abdômen proeminente e desnível de quadril) e membros inferiores (18% pés planos). Acredita-se que as tendências posturais detectadas podem ser conseqüência da repetição de movimentos técnicos, característicos do ballet clássico ao longo de anos de prática. Para prática com melhor desempenho, assim como duradoura (por muitos anos) e com menores riscos de se adquirir distúrbios orgânicos, acredita-se que o desenvolvimento de aptidão física geral e específica, assim como trabalhos de compensação poderiam ser importantes nas aulas de ballet.